منظمات الأعمال الجزائرية والمسؤولية الاجتماعية التحديات وسبل التقدم _دراسة استكشافية. - شريط, كمال; خلوفي, سفيان (جامعة الوادي - University of Eloued, 2020)
تهدف هذه الدراسة إلى التعرف على واقع تطبيق مفهوم المسؤولية الاجتماعية في منظمات الأعمال الجزائرية، وذلك من خلال دراسة استكشافية، ولتحقيق أهداف الدراسة تم التطرق إلى معايير ودوافع المسؤولية الاجتماعية لمنظمات الأعمال في الجزائر، وكذا تحديد الأولويات التي تتعلق بالقضايا الاجتماعية والبيئية في الجزائر، وصولا إلى تقييم وتحليل تجاوب قطاع الأعمال الحالي مع قضايا المجتمع والبيئة وتحدياته. ولقد أظهرت الدراسة في الأخير أن مفهوم المسؤولية الاجتماعية لا يزال غامض داخل منظمات الأعمال الجزائرية، كما أظهرت أن تجاوب قطاع الأعمال الحالي مع قضايا المجتمع والبيئة جد ضعيف، ويحتاج إلى مزيد من الجهود الإضافية. الكلمات المفتاح: مسؤولية اجتماعية ؛ منظمات أعمال ؛ قضايا مجتمع ؛ قضايا بيئة ؛ الجزائر. تصنيف JEL : M14. Abstract: This study aims to identify the reality of the application of the concept of social responsibility in Algerian business organizations through an exploratory study. In order to achieve the objectives of the study, the criteria and motives of social responsibility for business organizations in Algeria were discussed, as well as priorities for social and environmental issues in Algeria. Assessing and analyzing the current business response to community issues and the environment and its challenges. Finally, the study showed that the concept of social responsibility is a mystery in Algerian business organizations. It also showed that the current business response to society and environment issues is very weak and needs further efforts. Keywords: Social responsibility ; Business organizations ; Community issues ; Environmental issues ; Algeria Jel Classification Codes : M14.
Algerian Business Organizations and Social Responsibility Challenges and Ways of Progress - Exploratory Study
Keywords: مسؤولية اجتماعية ؛ منظمات أعمال ؛ قضايا مجتمع ؛ قضايا بيئة ؛ الجزائر.